Answer:
The value of f(-3) will be y=-5. (option C)
Explanation:
To find the value of f(3) we could first state the expression for f(x). The expression for y=f(x) can be determined by the following formula:
y-yo=m(x-xo)
The values of xo and yo are the coordinates of whichever of the known point, and m is the slope of linear function:
m=(y1-yo)/(x1-xo)
There y1, x1 is the coordintes of a different point. Choosing the points like:
(xo,yo)=(-2,-2)
(x1,y1)=(4,16)
The value of m results:
m=[16-(-2)]/[4-(-2)] = [18/6] = 3
Then by replacing m and (xo,yo) in the equation of y:
y-(-2)=3(x-(-2))
y+2=3(x+2)
f(x)=y=3x+6-2
f(x)=y=3x+4
Finally we replace the value of x=-3:
f(-3)=y=3(-3)+4
f(-3)=y=-9+4=-5